(untitled) (Journal of National Institute of Ophthalmology, 2026)
Background: Glaucoma is a major cause of irreversible blindness worldwide, greatly affecting vision and quality of life. This study aimed to assess visual outcomes and intraocular pressure changes following combined trabeculectomy and manual small-incision cataract surgery in patients with significant cataract and coexisting glaucoma whose pressure was uncontrolled or who poorly tolerated or complied with medications. Methods: This prospective observational case series study at the Department of Glaucoma, National Institute of Ophthalmology and Hospital, Bangladesh (July 2021–June 2022), included 80 patients with significant cataract and POAG or PACG. Patients underwent combined MSICS with PMMA IOL and mitomycin-C–assisted trabeculectomy performed by fellowship-trained surgeons. BCVA, IOP, optic nerve status, bleb morphology, complications, and additional interventions were recorded preoperatively and up to 6 months postoperatively. Data were analyzed using SPSS v16 (paired t-test, p < 0.05). Results: Among 80 patients (42 PACG, 38 POAG; mean age 60.1 ± 8.8 years), most had nuclear cataract (85%) and moderate to advanced glaucoma. At six months, 90% achieved BCVA of 6/6–6/18, mean IOP decreased by 16.6 ± 7.5 mmHg, Intra- and postoperative complications occurred in 15% and 27.5% of eyes, respectively, with PCO being the most common (11.2%). Conclusion: This study shows that performing combined trabeculectomy and cataract surgery at the same setting is an effective approach for patients with coexisting glaucoma and cataract. J.Natl.Inst.Ophthalmol.2024;7(2): 47-56